Integrated CIRCLE-seq with RNA-seq to decipher the quantity, localization, and functional features of eccDNA in AML - Gao, Lijuan; Lu, Qiongyu; Li, Hao; Ruan, Changgen; Zeng, Zhao; Chen, Suning (Frontiers in Oncology, 2025)
BackgroundExtrachromosomal circular DNA (eccDNA) plays critical roles in cancer, yet its landscape in acute myeloid leukemia (AML) remains unexplored.MethodsWe used CIRCLE-seq and RNA-seq to characterize eccDNA in 12 AML patients and 4 healthy controls.ResultsAML cells showed significantly increased eccDNA counts and gene involvement versus healthy controls, with distinct size peaks at 202 and 368 bp. eccDNAs localized non-randomly to chromosomes 1, 2, and 10–19, enriching near transcription start sites and regulatory regions. Functional analysis revealed activation of oncogenic pathways (e.g., MAPK, ErbB signaling) in AML-associated eccDNA. Integrative analysis identified 570 genes upregulated at both the eccDNA and mRNA levels, including myeloid leukemia-related genes (e.g., FLT3, RUNX1, and CD33) and oncogenes. Prognostic analysis showed that high expression of these genes correlated with poor outcomes in AML.ConclusionsThis study unveils the eccDNA landscape in AML by direct CIRCLE-seq, linking its accumulation to transcriptional dysregulation and leukemogenesis, and highlights eccDNA as a potential biomarker and therapeutic target.